Gene expression and evolution of Bowman-Birk protease inhibitors in wild and domesticated Vigna (Fabaceae) species - Toini, Elisa; Totaro, Maria; Silvestri, Giuseppe; Vertemara, Jacopo; Zecca, Giovanni; Panzeri, Davide; Palm, Emily Rose; Wagensommer, Robert Philipp; Zampella, Giuseppe; Labra, Massimo; Grassi, Fabrizio (Frontiers in Plant Science, 2026)
Bowman-Birk protease inhibitors (BBIs) are multifunctional proteins with a double-headed structure, featuring two distinct inhibitory loops that target trypsin and chymotrypsin proteases. BBI regulates protease activity in plants and provides defense against pests and pathogens, but little is still known about their expression levels and their ability to interact with natural targets. Our results showed that BBI1 and BBI2 genes are the most highly expressed in Vigna seeds. Consequently, we produced two multiple sequence alignments including homologs from 42 Vigna taxa to explore variability and functionality. Phylogenetic relationships, signals of positive selection, and interaction energy levels with their natural targets were inferred. Overall, BBI2 exhibited the highest affinity for the assessed targets compared to BBI1. Amino acid substitutions have led to distinct protein variants across species, each displaying different interaction capacities with their respective targets. Additionally, the residue conferring inhibitory specificity for trypsin, located in the first domain, was found to be under positive selection in both genes. This suggests an ongoing evolutionary process aimed at optimizing affinity with proteases through continuous adaptation. Finally we emphasize that findings obtained can be used to drive the activity of plant breeders and more efficient cultivars can be selected. Given the growing availability of genomic information of wild and domesticated accessions, docking simulations offer a convenient and effective method to preliminarily assess new protein variants.